Investment and patent licensing in the value chain - Gerard Llobet; Damien J. Neven (Graduate Institute of International and Development Studies, 2022)
At which stage in the production chain should patent licensing takes place? In this paper we show that under realistic circumstances a patent holder would be better off by licensing downstream. This occurs when the licensing revenue can depend on the downstream value of the product either directly or through the use of ad-valorem royalties. We show that the results are similar when, instead, we assume that the downstream licensee is less informed about the validity of the patent. In most cases, downstream licensing increases allocative efficiency. However, it might reduce the incentives to invest by the manufacturers and thereby reduce welfare. We characterize the circumstances under which a conflict arises between the stage at which patent holders prefer to license their technology and the stage at which it is optimal from a social standpoint that licensing takes place.
Keywords: L15; L24; O31; O34; 330; Royalty Neutrality; Standard Setting Organizations; Patent Licensing; R&D Investment